laminate

JP2025027551APending Publication Date: 2025-02-28MITSUI CHEMICALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023132376
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-28

AI Technical Summary

Benefits of technology

【0017】 本発明により、基材層とトップ層とを有する積層体において、より幅広い種類の基材層やトップ層に適用できる接着層、および、該接着層を介した基材層とトップ層との密着性に優れた積層体が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025027551000001
    Figure 2025027551000001
  • Figure 2025027551000002
    Figure 2025027551000002
  • Figure 2025027551000003
    Figure 2025027551000003
Patent Text Reader

Abstract

To provide a laminate including an adhesive layer which can be applied to wide kinds of substrate layers and top layers and having elevated adhesion between the adhesive layer and the top layer via substrate layer.SOLUTION: A laminate is a laminate where a substrate layer (I), a primer layer (II), and a top layer (III) are laminated in this order, wherein the primer layer (II) includes a modified 4- methyl-1-pentene-based polymer (A) satisfying requirements (A-1) and (A-3). (A-1) an amount of a constitutional unit (i) derived from 4-methyl-1-pentene (U1) is 84.0-100.0 mol% and a total amount (U2) of a constitutional unit (ii) derived from α-olefin having a carbon number of 2-20 (excluding 4-methyl-1-pentene) is 16.0-0.0 mol% (the sum of the U1 and the U2 is 100.0 mol%). (A-3) a melting point (Tm) measured by differential scanning calorimetry (DSC) is over 180°C and 220°C or under.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate. [Background technology]

[0002] 4-Methyl-1-pentene polymers have low polarity and excellent mold releasability. Therefore, when a molded article made of 4-methyl-1-pentene polymer is painted, the adhesive strength of the paint may be insufficient.

[0003] As a means for solving this problem, for example, Patent Documents 1 and 2 disclose that the interlaminar strength between a base material layer and a synthetic resin layer that have been subjected to an Itro treatment is excellent. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-65270 A [Patent Document 2] JP 2016-168849 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the ITO process, since the substrate is treated using a flame, the substrate may be deformed or the properties of the substrate may be damaged by heat. In addition, the ITO process is difficult to apply to thin molded bodies that are more easily deformed. Therefore, there is a demand for an adhesive layer that can be applied to a wider variety of substrate layers and top layers, including the substrate layers and top layers of these molded bodies to which the ITO process is difficult to apply, and a laminate to which the adhesive layer is applied.

[0006] In view of such conventional technology, an object of the present invention is to provide an adhesive layer that can be applied to a wider variety of base layers and top layers, and a laminate in which the adhesion between the base layer and the top layer is enhanced via the adhesive layer. [Means for solving the problem]

[0007] The present invention relates to, for example, the following [1] to [9].

[0008] [1] A laminate comprising a base layer (I), a primer layer (II), and a top layer (III) laminated in this order, The primer layer (II) comprises a modified 4-methyl-1-pentene polymer (A) that satisfies the following requirements (A-1) and (A-3): (A-1) The amount (U1) of the structural unit (i) derived from 4-methyl-1-pentene is 84.0 to 100.0 mol %, and the total amount (U2) of the structural units (ii) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 16.0 to 0.0 mol % (the total of U1 and U2 is 100.0 mol %). (A-3) The melting point (Tm) measured by differential scanning calorimetry (DSC) is greater than 180°C and less than 220°C.

[0009] [2] The laminate according to [1], wherein the graft modification amount of the modified 4-methyl-1-pentene polymer (A) is more than 0.0 mass % and not more than 5.0 mass %.

[0010] [3] The laminate according to [1] or [2], wherein the α-olefin (excluding 4-methyl-1-pentene) from which the structural unit (ii) is derived has 4 to 20 carbon atoms.

[0011] [4] The laminate according to any one of [1] to [3], wherein U1 is 92.5 to 97.1 mol % and U2 is 7.5 to 2.9 mol % (wherein the sum of U1 and U2 is 100.0 mol %).

[0012] [5] The laminate according to any one of [1] to [4], wherein the modified 4-methyl-1-pentene polymer (A) satisfies at least one of the following requirements (A-4) and (A-5): (A-4) In the measurement of the melting point (Tm) by differential scanning calorimetry (DSC), the endothermic end temperature (TmE) in the melting (endothermic) curve is 230°C or lower. (A-5) In the measurement of the melting point (Tm) by a differential scanning calorimeter (DSC), the heat generation onset temperature (TcS) in the crystallization (heat generation) curve is 210°C or lower.

[0013] [6] The laminate according to [5], wherein the modified 4-methyl-1-pentene polymer (A) satisfies the requirements (A-4) and (A-5).

[0014] [7] The laminate according to any one of [1] to [6], wherein the modified 4-methyl-1-pentene polymer (A) satisfies the following requirement (A-2): (A-2) The intrinsic viscosity [η] measured in decalin at 135°C is in the range of 0.5 to 6.0 dl / g.

[0015] [8] The laminate according to any one of [1] to [7], wherein the base layer (I) contains at least one selected from the group consisting of a resin, a metal, and a prepreg.

[0016] [9] The laminate according to any one of [1] to [8], wherein the top layer (III) contains at least one selected from the group consisting of a resin, a metal, and a prepreg. Effect of the Invention

[0017] The present invention provides a laminate having a base layer and a top layer, which has an adhesive layer that can be applied to a wider variety of base layers and top layers, and which has excellent adhesion between the base layer and the top layer via the adhesive layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present invention will now be described in further detail. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits.

[0019] [Laminate] The laminate of the present invention is a laminate in which a substrate layer (I), a primer layer (II) and a top layer (III) are laminated in this order.

[0020] <Base material layer (I)> The material constituting the base layer (I) is not particularly limited, and examples thereof include resins (e.g., urethane resins, polycarbonate resins, fluororesins, silicone resins, polymethacrylate resins, polystyrene resins, polyester resins, polyolefin resins, epoxy resins, melamine resins, triacetyl cellulose resins, ABS resins, AS resins, and norbornene resins, as well as the synthetic resins described in paragraphs

[0052] to

[0107] of JP 2017-65270 A (which overlap with the above-mentioned resin materials), wood, paper, glass, metal, and prepregs. Among these, it is preferable to include at least one selected from the group consisting of resins, metals, and prepregs, and it is more preferable to include at least one selected from the group consisting of resins (excluding 4-methyl-1-pentene polymers), metals, and prepregs. Here, the prepreg refers to a structure including a fiber base material and a resin composition impregnated into the fiber base material.

[0021] When the material constituting the substrate layer (I) is a resin, it may contain additives that have been conventionally blended into resin compositions and their molded products (films, etc.) within the scope that does not impair the effects of the present invention. Examples of additives include antioxidants, heat stabilizers, weather stabilizers, antistatic agents, slip agents, leveling agents, reinforcing agents, antiblocking agents, antifogging agents, lubricants, dyes, pigments, natural oils, synthetic oils, waxes, and fillers.

[0022] The substrate layer (I) can be formed from the above-mentioned materials by a conventionally known method. The thickness of the substrate layer (I) is usually about 0.01 to 10,000 μm, but is not particularly limited.

[0023] <Primer layer (II)> The primer layer (II) contains a modified 4-methyl-1-pentene polymer (A) that satisfies the following requirements (A-1) and (A-3).

[0024] The modified 4-methyl-1-pentene polymer (A) is a general term for modified homopolymers of 4-methyl-1-pentene and modified copolymers of 4-methyl-1-pentene and α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene).

[0025] In the following description, in the 4-methyl-1-pentene polymer or modified 4-methyl-1-pentene polymer (A), a structural unit derived from 4-methyl-1-pentene may be referred to as a "structural unit (i)", and a structural unit derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) may be referred to as a "structural unit (ii)".

[0026] Requirement (A-1): Requirement (A-1) is that the amount (U1) of the structural units (i) derived from 4-methyl-1-pentene is 84.0 to 100.0 mol %, and the total amount (U2) of the structural units (ii) derived from α-olefins having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 16.0 to 0.0 mol % (the sum of U1 and U2 is 100.0 mol %).

[0027] The amount of the structural units (U1) is preferably 84.0 to 100.0 mol%, more preferably 90.0 to 99.0 mol%, and even more preferably 92.5 to 97.1 mol%. The total amount of the structural units (U2) is preferably 0.0 to 16.0 mol%, more preferably 10.0 to 1.0 mol%, and even more preferably 7.5 to 2.9 mol%. The U1 and U2 can be determined by the method employed in the examples described below.

[0028] The U1 and U2 in the modified 4-methyl-1-pentene polymer (A) are almost the same as the amount of the structural unit (i) and the total amount of the structural unit (ii) contained in the unmodified 4-methyl-1-pentene polymer to be graft-modified. Therefore, the U1 and U2 in the modified 4-methyl-1-pentene polymer (A) are adjusted by selecting the composition of the unmodified 4-methyl-1-pentene polymer to be graft-modified.

[0029] Since the modified 4-methyl-1-pentene polymer (A) satisfies the requirement (A-1), in the laminate of the present invention having the primer layer (II) containing the modified 4-methyl-1-pentene polymer (A), good adhesion between the substrate layer (I) and the top layer (III) tends to be exhibited without impairing the properties (e.g., heat resistance) of the substrate layer (I). In addition, when preparing a coating agent for producing the primer layer (II), the modified 4-methyl-1-pentene polymer (A) is easily dissolved in a solvent that can be used to prepare a coating agent containing the modified 4-methyl-1-pentene polymer (A), and the properties of the coating agent tend to be uniform.

[0030] Examples of the α-olefin include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 3-methyl-1-pentene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and 1-eicosene.

[0031] Among these, α-olefins having 4 to 20 carbon atoms are preferred, and from the viewpoint of heat resistance, linear α-olefins having 4 to 20 carbon atoms are more preferred, and linear α-olefins having 6 to 18 carbon atoms are even more preferred. Specifically, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, and the like are preferred, and among these, 1-decene, 1-hexadecene, and 1-octadecene are particularly preferred. The α-olefin having 2 to 20 carbon atoms may be used alone or in combination of two or more kinds.

[0032] The modified 4-methyl-1-pentene polymer (A) may further contain a structural unit other than the structural unit (i) and the structural unit (ii) (hereinafter referred to as "structural unit (iii)") in a small amount that does not impair the effects of the present invention, specifically, in a range of 10 mol % or less, preferably 5 mol % or less, and more preferably 3 mol % or less, relative to 100 mol % in total of the structural unit (i) and the structural unit (ii). The structural unit (iii) may be of one type alone, or of two or more types in combination.

[0033] Specific preferred examples of polymerizable monomers from which the structural unit (iii) is derived include vinyl compounds having a cyclic structure, such as styrene, vinylcyclopentane, vinylcyclohexane, and vinylnorbornane; vinyl esters, such as vinyl acetate; unsaturated organic acids or derivatives thereof, such as maleic anhydride; conjugated dienes, such as butadiene, isoprene, pentadiene, and 2,3-dimethylbutadiene; 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, and the like. Examples of non-conjugated polyenes include butadiene, dicyclopentadiene, cyclohexadiene, dicyclooctadiene, methylenenorbornene, 5-vinyl-2-norbornene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, 5-isopropylidene-2-norbornene, 6-chloromethyl-5-isopropenyl-2-norbornene, 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, and 2-propenyl-2,2-norbornadiene.

[0034] Requirement (A-3): Requirement (A-3) is that the melting point (Tm) measured by a differential scanning calorimeter (DSC) under the conditions employed in the examples described below is more than 180° C. and not more than 220° C. The melting point is preferably 187 to 215°C, more preferably 188 to 214°C, and further preferably 198 to 213°C.

[0035] Since the modified 4-methyl-1-pentene polymer (A) satisfies the requirement (A-3), in the laminate of the present invention having the primer layer (II) containing the modified 4-methyl-1-pentene polymer (A), the properties (e.g., heat resistance) of the base layer (I) are not impaired, and the adhesion between the base layer (I) and the top layer (III) is good. The reason for the good adhesion is considered to be that when preparing the coating agent for producing the primer layer (II), the modified 4-methyl-1-pentene polymer (A) is easily dissolved in a solvent that can be used to prepare the coating agent containing the modified 4-methyl-1-pentene polymer (A), and the properties of the coating agent, etc. become uniform. On the other hand, if the melting point (Tm) is greater than the upper limit, the modified 4-methyl-1-pentene polymer (A) is difficult to dissolve in a solvent that can be used to prepare a coating agent containing the modified 4-methyl-1-pentene polymer (A), making it difficult to prepare a uniform coating agent. Even if a primer layer is formed from the coating agent, it is difficult to increase the adhesion between the base layer (I) and the top layer (III).

[0036] The melting point (Tm) value tends to depend on the stereoregularity of the modified 4-methyl-1-pentene polymer (A) and the total amount (U2) of the structural units (ii) in the modified 4-methyl-1-pentene polymer (A). Here, the stereoregularity of the modified 4-methyl-1-pentene polymer (A) and the total amount (U2) of the structural units (ii) depend on the stereoregularity and the amount of the structural units (ii) in the unmodified 4-methyl-1-pentene polymer to be graft-modified. Therefore, when polymerizing the unmodified 4-methyl-1-pentene polymer to be graft-modified, the melting point (Tm) can be adjusted by using an olefin polymerization catalyst described later and further controlling the total amount (U2) of the structural units (ii).

[0037] The modified 4-methyl-1-pentene polymer (A) preferably satisfies at least one of the following requirements (A-2), (A-4) to (A-6), more preferably satisfies (A-4) or (A-5), further preferably satisfies (A-4) and (A-5), particularly preferably satisfies (A-2), (A-4) and (A-5), and particularly preferably satisfies all of (A-2), (A-4) to (A-6).

[0038] Requirement (A-2): The requirement (A-2) is that the modified 4-methyl-1-pentene polymer (A) has an intrinsic viscosity [η] of 0.5 to 6.0 dl / g, as measured in decalin at 135° C. by the method described in the Examples below. The intrinsic viscosity [η] is preferably 0.7 to 5.5 dl / g, more preferably 0.7 to 5.0 dl / g, further preferably 0.8 to 4.0 dl / g, and particularly preferably 0.8 to 2.5 dl / g.

[0039] When the modified 4-methyl-1-pentene polymer (A) satisfies the requirement (A-2), it has better heat resistance. In addition, when preparing a coating agent for preparing a primer layer (II), the modified 4-methyl-1-pentene polymer (A) that satisfies the requirement (A-2) is easily dissolved in a solvent that can be used to prepare a coating agent containing the modified 4-methyl-1-pentene polymer (A), and the properties of the coating agent tend to be uniform. As a result, the primer layer (II) formed from the coating agent containing the modified 4-methyl-1-pentene polymer (A) that satisfies the requirement (A-2) can better adhere the substrate layer (I) and the top layer (III).

[0040] Moreover, a coating agent containing the modified 4-methyl-1-pentene polymer (A) satisfying the requirement (A-2) has good coatability and is suitable for forming a coating layer. The intrinsic viscosity [η] can be adjusted, for example, by the amount of hydrogen added in the polymerization step when producing an unmodified 4-methyl-1-pentene polymer that is the raw material for the modified 4-methyl-1-pentene polymer (A).

[0041] Requirement (A-4): The requirement (A-4) is that, in the measurement of the melting point (Tm) by the above-mentioned differential scanning calorimeter (DSC), the endothermic end temperature (TmE) in the melting (endothermic) curve is 230°C or lower. The endothermic end temperature (TmE) is preferably less than 230°C, more preferably less than 228°C, and further preferably less than 228°C, and the lower limit may be, for example, 190°C or higher. The endothermic end temperature means the temperature at which melting is completed. The endothermic end temperature and the heat generation start temperature described later are indicators different from the onset and offset, which are generally the intersection points between the baseline and the tangent to the steady line.

[0042] The endothermic end temperature can be adjusted to a desired value, for example, by appropriately selecting an olefin polymerization catalyst for polymerizing an unmodified 4-methyl-1-pentene polymer that is a raw material for the modified 4-methyl-1-pentene polymer (A) and by controlling the content of the structural unit (ii).

[0043] The modified 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range has excellent heat resistance. Therefore, the primer layer (II) formed from a coating agent or the like containing the modified 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range also tends to have excellent heat resistance. In addition, the modified 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range is more easily dissolved in a solvent that can be used when preparing a coating agent containing the modified 4-methyl-1-pentene polymer (A) than a modified 4-methyl-1-pentene polymer having an endothermic end temperature not in the above range. Therefore, the properties of the coating agent or the like prepared using the modified 4-methyl-1-pentene polymer (A) having an endothermic end temperature in the above range tend to be uniform. As a result, the primer layer (II) formed from a coating agent or the like containing the modified 4-methyl-1-pentene polymer (A) can adhere to the substrate layer (I) and the top layer (III).

[0044] Requirement (A-5): The requirement (A-5) is that, in the measurement of the melting point (Tm) by the above-mentioned differential scanning calorimeter (DSC), the heat generation onset temperature (TcS) in the crystallization (exothermic) curve is 210° C. or less. The heat generation onset temperature (TcS) is preferably less than 210° C., more preferably less than 200° C., and even more preferably less than 200° C., and the lower limit thereof may be, for example, 140° C. or more.

[0045] The heat generation initiation temperature can be adjusted to a desired value, for example, by appropriately selecting an olefin polymerization catalyst for polymerizing an unmodified 4-methyl-1-pentene polymer that is a raw material for the modified 4-methyl-1-pentene polymer (A) and by controlling the content of the structural unit (ii).

[0046] The modified 4-methyl-1-pentene polymer (A) having a heat generation start temperature in the above range has excellent heat resistance. Therefore, the primer layer (II) formed from a coating agent or the like containing the modified 4-methyl-1-pentene polymer (A) having a heat generation start temperature in the above range also tends to have excellent heat resistance. In addition, the modified 4-methyl-1-pentene polymer (A) having a heat generation start temperature in the above range is more easily dissolved in a solvent that can be used when preparing a coating agent containing the modified 4-methyl-1-pentene polymer (A) than a modified 4-methyl-1-pentene polymer having a heat generation start temperature not in the above range. Therefore, the properties of the coating agent or the like prepared using the modified 4-methyl-1-pentene polymer (A) having a heat generation start temperature in the above range tend to be uniform. As a result, the primer layer (II) formed from a coating agent or the like containing the modified 4-methyl-1-pentene polymer (A) can adhere to the base layer (I) and the top layer (III).

[0047] Requirement (A-6): The requirement (A-6) is that the crystallization temperature (Tc) in the crystallization (exothermic) curve in the measurement of the melting point (Tm) by the above-mentioned differential scanning calorimeter (DSC) is 110 to 220° C. The crystallization temperature (Tc) is preferably 120 to 210° C., more preferably 130 to 200° C.

[0048] The crystallization temperature can be adjusted to a desired value, for example, by appropriately selecting an olefin polymerization catalyst for polymerizing an unmodified 4-methyl-1-pentene polymer that is a raw material for the modified 4-methyl-1-pentene polymer (A) and by controlling the content of the structural unit (ii).

[0049] The modified 4-methyl-1-pentene polymer (A) having a crystallization temperature in the above range has excellent heat resistance. Therefore, the primer layer (II) formed from a coating agent or the like containing the modified 4-methyl-1-pentene polymer (A) having a crystallization temperature in the above range also tends to have excellent heat resistance. In addition, the modified 4-methyl-1-pentene polymer (A) having a crystallization temperature in the above range is more easily dissolved in a solvent that can be used when preparing a coating agent containing the modified 4-methyl-1-pentene polymer (A) than a modified 4-methyl-1-pentene polymer having a crystallization temperature not in the above range. Therefore, the properties of the coating agent or the like prepared using the modified 4-methyl-1-pentene polymer (A) having a crystallization temperature in the above range tend to be uniform. As a result, the primer layer (II) formed from a coating agent or the like containing the modified 4-methyl-1-pentene polymer (A) can adhere to the base layer (I) and the top layer (III).

[0050] (Method for producing modified 4-methyl-1-pentene polymer (A)) The modified 4-methyl-1-pentene polymer (A) can be produced, for example, by polymerizing 4-methyl-1-pentene, an α-olefin having 2 to 20 carbon atoms which optionally derives the structural unit (ii), and a polymerizable monomer which optionally derives the structural unit (iii) in the presence of an olefin polymerization catalyst by a known method to obtain an unmodified 4-methyl-1-pentene polymer, and then modifying the unmodified 4-methyl-1-pentene polymer.

[0051] Examples of the catalyst for olefin polymerization include metallocene catalysts.Preferred metallocene catalysts include those described in WO 01 / 53369, WO 01 / 27124, JP 3-193796, JP 02-41303, WO 06 / 025540, or WO 2014 / 123212.

[0052] (Modified 4-methyl-1-pentene polymer) The modified 4-methyl-1-pentene polymer (A) is a 4-methyl-1-pentene polymer modified, preferably a polymer modified with a functional group, and more preferably a graft modified product.

[0053] For example, an ethylenically unsaturated monomer having a functional group is used for the modification of the 4-methyl-1-pentene polymer. The ethylenically unsaturated monomer used for the modification is preferably an unsaturated carboxylic acid and / or a derivative thereof. Examples of the unsaturated carboxylic acid and / or a derivative thereof include an unsaturated compound having one or more carboxylic acid groups, an ester of a compound having a carboxylic acid group and an alkyl alcohol, and an unsaturated compound having one or more carboxylic acid anhydride groups.

[0054] Examples of the unsaturated group of the unsaturated compound include a vinyl group, a vinylene group, and an unsaturated cyclic hydrocarbon group. The unsaturated carboxylic acid and / or its derivative can be used alone or in combination of two or more. Among these ethylenically unsaturated monomers, unsaturated dicarboxylic acids or their acid anhydrides are preferred, and maleic acid, nadic acid, or their acid anhydrides are particularly preferred.

[0055] The method for graft-modifying a 4-methyl-1-pentene polymer with an ethylenically unsaturated monomer is not particularly limited, and any conventionally known graft polymerization method such as a solution method, a melt kneading method, etc., can be used. For example, there is a method in which a 4-methyl-1-pentene polymer is melted and an ethylenically unsaturated monomer is added to perform graft modification, or a method in which a 4-methyl-1-pentene polymer is dissolved in a solvent to form a solution and an ethylenically unsaturated monomer is added thereto to perform graft modification.

[0056] When the modified 4-methyl-1-pentene polymer (A) is a graft-modified product, the amount of graft modification measured by the method employed in the examples described later is preferably more than 0.0% by mass and not more than 5.0% by mass, more preferably 0.1 to 5.0% by mass, further preferably 0.4 to 3.0% by mass, and particularly preferably 0.5 to 2.5% by mass. When the amount of graft modification of the modified 4-methyl-1-pentene polymer (A) is within the above range, the adhesion between the base layer (I) and the top layer (III) tends to be excellent.

[0057] The primer layer (II) may contain additives that have been conventionally blended into resin films, as long as the effects of the present invention are not impaired. Examples of the additives include those exemplified as additives that may be added to the substrate layer (I) described above.

[0058] The thickness of the primer layer (II) is preferably thin, for example, 500 μm or less, preferably 100 μm or less, preferably 10 μm or less, more preferably 1 μm or less. The lower limit of the thickness of the primer layer (II) is not particularly limited, but is usually 0.01 μm or more, preferably 0.1 μm or more. When the thickness of the primer layer (II) is within the above range, the adhesion between the base layer (I) and the top layer (III) tends to be excellent.

[0059] [Isocyanate compounds] The primer layer (II) may contain an isocyanate compound. The isocyanate compound is not particularly limited as long as it is a compound having an isocyanate group, but from the viewpoint of improving the adhesion between the primer layer (II) and the base layer (I), it is preferable that the isocyanate compound is a polyfunctional isocyanate compound having two or more isocyanate groups in one molecule.

[0060] Examples of bifunctional isocyanate compounds having two isocyanate groups in one molecule include aliphatic diisocyanates such as methylene diisocyanate, dimethylene diisocyanate, trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, dipropyl ether diisocyanate, 2,2-dimethylpentane diisocyanate, 3-methoxyhexane diisocyanate, octamethylene diisocyanate, 2,2,4-trimethylpentane diisocyanate, nonamethylene diisocyanate, decamethylene diisocyanate, 3-butoxyhexane diisocyanate, 1,4-butylene glycol dipropyl ether diisocyanate, and thiodihexyl diisocyanate; Aromatic diisocyanates such as m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, dimethylbenzene diisocyanate, ethylbenzene diisocyanate, isopropylbenzene diisocyanate, tolidine diisocyanate, 1,4-naphthalene diisocyanate, 1,5-naphthalene diisocyanate, 2,6-naphthalene diisocyanate, 2,7-naphthalene diisocyanate, metaxylylene diisocyanate, paraxylylene diisocyanate, and tetramethylxylylene diisocyanate; and Examples of the diisocyanate include alicyclic diisocyanates such as hydrogenated xylylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate.

[0061] The isocyanate compound may be a biuret or isocyanurate, which is a trimer of a difunctional isocyanate compound, an adduct between a polyol such as trimethylolpropane and a difunctional isocyanate compound (i.e., an adduct), or an adduct between an alcohol such as methanol and a difunctional isocyanate compound (i.e., an allophanate).

[0062] Among these, from the viewpoints of adhesion between the primer layer (II) and the base layer (I) and heat resistance of the primer layer (II), the isocyanate compound is preferably an aliphatic isocyanate compound, more preferably an aliphatic isocyanate compound having two or more isocyanate groups in one molecule, further preferably an aliphatic diisocyanate, an isocyanurate of an aliphatic diisocyanate, an allophanate of an aliphatic diisocyanate and an alcohol, or an adduct of an aliphatic diisocyanate and a polyol, and particularly preferably an aliphatic diisocyanate or an isocyanurate of an aliphatic diisocyanate.

[0063] The isocyanate compound may be a commercially available product. Examples of commercially available products include the Takenate series (manufactured by Mitsui Chemicals, Inc.), such as Takenate D103H, D204, D160N, D170N, D165N, D178NL, D110N, and D370N, and Coronate HX, HXR, HXL, HXLV, HK, HK-T, HL, and 2096 (manufactured by Nippon Polyurethane Industry Co., Ltd.).

[0064] When the primer layer (II) contains an isocyanate compound, the content is usually 2.00 parts by mass or less, preferably 1.50 parts by mass or less, based on 100 parts by mass of the modified 4-methyl-1-pentene polymer (A). When the primer layer (II) contains an isocyanate compound, the lower limit of the content of the isocyanate compound is not particularly limited, but is usually 0.001 parts by mass or more based on 100 parts by mass of the modified 4-methyl-1-pentene polymer (A). The isocyanate compound may be contained in the primer layer (II) either alone or in combination of two or more kinds.

[0065] (Method of forming primer layer (II)) The method for forming the primer layer (II) is not particularly limited, and may be, for example, a method in which a coating agent (application liquid) containing the modified 4-methyl-1-pentene polymer (A), a solvent, and optionally one or more selected from the group consisting of an isocyanate compound and an additive is prepared, and the coating agent is applied to the substrate layer (I) and dried.

[0066] The solvent used in the preparation of the coating agent is not particularly limited as long as it can dissolve the 4-methyl-1-pentene polymer (A). Among them, organic solvents can be preferably used. Examples of the solvent include aliphatic hydrocarbons such as n-hexane, n-heptane, n-octane, cyclohexane, methylcyclohexane, and ethylcyclohexane; aromatic hydrocarbons such as toluene and xylene; esters such as ethyl acetate and butyl acetate; and mixed solvents containing two or more selected from the group consisting of the aliphatic hydrocarbons, aromatic hydrocarbons, and esters. Among them, toluene, cyclohexane, methylcyclohexane, and mixed solvents of these solvents and ethyl acetate can be preferably used.

[0067] When the coating agent contains an isocyanate compound, the adhesion between the primer layer (II) containing the isocyanate compound and the substrate layer (I) can be improved by performing a heat treatment (aging treatment) for a certain time when forming the primer layer (II). The time and temperature of the aging treatment are not particularly limited, but an example of the aging treatment is a treatment in which the substrate layer (I) to which the primer layer (II) is attached is heated to 80°C for 20 hours. In addition, a treatment in which the coating agent is applied to the substrate layer (I) and then dried at 80°C for 20 hours may be used as the aging treatment. When the substrate layer (I) is a material that is heat-treated such as a prepreg, the substrate layer (I) after application of the coating agent can be heat-treated to heat the substrate layer (I), form the primer layer (II) by drying the coating agent, and perform the aging treatment at the same time.

[0068] <Top layer (III)> The top layer (III) is the outermost layer of the laminate of the present invention.

[0069] The material constituting the top layer (III) is not particularly limited, and examples thereof include resins (for example, resin materials such as urethane resins, polycarbonate resins, fluororesins, silicone resins, polymethacrylate resins, polystyrene resins, polyester resins, polyolefin resins, epoxy resins, melamine resins, triacetyl cellulose resins, ABS resins, AS resins, and norbornene resins, and the synthetic resins described in

[0052] to

[0107] of JP2017-65270A (which overlap with the above-mentioned resin materials), wood, paper, glass, metal, and prepregs. Among these, it is preferable that the material contains at least one selected from the group consisting of resins, metals, and prepregs, and it is more preferable that the material contains at least one selected from the group consisting of resins (excluding urethane acrylic resins), metals, and prepregs.

[0070] When the material constituting the top layer (III) is a resin, it may contain additives that have been conventionally blended into resin compositions and their molded products (films, etc.) within the range that does not impair the effects of the present invention. Examples of additives include those exemplified as additives that may be added to the above-mentioned base layer (I).

[0071] The top layer (III) can be formed from the above-mentioned materials by a conventionally known method. The thickness of the top layer (III) can be appropriately designed according to the type and shape of the material constituting the top layer (III) and the use of the laminate, and is not particularly limited. For example, the top layer (III) may be a resin film, a metal sheet, a prepreg, a molded body including a resin injection molded body, a metal plate, etc. As described above, the shape of the top layer (III) may be various, but the thickness of the top layer (III) is, for example, 0.01 μm or more and 50 mm or less, preferably 0.1 μm or more and 10 mm or less.

[0072] (Laminate) The laminate of the present invention is a laminate in which the above-mentioned base layer (I), primer layer (II) and top layer (III) constituting the outermost layer are laminated in this order.

[0073] Since the laminate of the present invention has the primer layer (II), the base layer (I) and the top layer (III) are adhered to each other with high strength. The laminate of the present invention may have any layer other than these three layers. From the viewpoint of obtaining high adhesion between the base layer (I) and the top layer (III) by the primer layer (II), the any layer is provided on the side of the base layer (I) opposite to the primer layer (II) side, not between these layers.

[0074] The thickness of the laminate of the present invention is usually about 0.01 to 100,000 μm, but is not particularly limited. The laminate of the present invention has the above-mentioned high adhesion and also has high scratch resistance due to the top layer, and is therefore useful for applications such as food containers, packaging materials, animal cages, laboratory instruments, optical components, and terahertz transmitting components. EXAMPLES

[0075] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the description of the following examples.

[0076] <Method of measuring physical properties of polymer> [composition] The amount of structural units (i) (the amount of structural units derived from 4-methyl-1-pentene, U1) and the total amount of structural units (ii) (the amount of structural units derived from α-olefin, U2) contained in the 4-methyl-1-pentene polymer or modified 4-methyl-1-pentene polymer (A) were determined by the following apparatus and conditions: 13 Calculated from C-NMR spectrum.

[0077] The nuclear magnetic resonance spectrometer used was a JEOL ECP500 type. The solvent was a mixture of o-dichlorobenzene / heavy benzene (80 / 20% by volume), the sample concentration was 55 mg / 0.6 mL, the measurement temperature was 120°C, and the observed nuclei were 13 The measurements were performed using C (125 MHz), a sequence of single pulse proton decoupling, a pulse width of 4.7 μs (45° pulse), a repetition time of 5.5 s, and an accumulation count of 10,000 or more, with 27.50 ppm as the reference value for the chemical shift. 13 The composition of 4-methyl-1-pentene and α-olefins was quantified by C-NMR spectroscopy. The total amount of the structural units (i) and (ii) was determined in the same manner for the polymer (CA) used in the comparative examples described below and the 4-methyl-1-pentene polymer used in the preparation of the polymer (CA).

[0078] [Intrinsic viscosity [η]] The intrinsic viscosity [η] was measured at 135° C. using decalin as a solvent. That is, about 20 mg of the sample 4-methyl-1-pentene polymer or modified 4-methyl-1-pentene polymer (A) was weighed out, dissolved in 15 mL of decalin, and the specific viscosity η sp The decalin solution was diluted with 5 mL of decalin solvent, and the specific viscosity η was measured in the same manner. sp This dilution procedure was repeated two more times, and the η sp The value of / C was calculated as the intrinsic viscosity (see the formula below). [η]=lim(η sp / C) (C→0) The intrinsic viscosity [η] of the polymer (CA) used in the comparative examples described later and the 4-methyl-1-pentene polymer used in the preparation of the polymer (CA) was also determined in the same manner.

[0079] [Graft modification amount] The amount of graft modification of the modified 4-methyl-1-pentene polymer (A) (i.e., the content of the structural units derived from the ethylenically unsaturated monomer used for modification when the mass of the modified 4-methyl-1-pentene polymer (A) is taken as 100% by mass) was determined by the following method. First, the modified 4-methyl-1-pentene polymer (A) as a sample was treated at 250°C with 5 minutes of preheating and 3 minutes of pressing to prepare a pressed film, and the pressed film was subjected to IR measurement by a transmission method using a Fourier transform infrared spectrophotometer (FT-IR410, manufactured by JASCO Corporation). In the following examples, maleic anhydride was used for graft modification, so that the peak at 1860 cm -1 and 4321 cm -1 The amount of graft modification was calculated from the peak intensity. The amount of graft modification of the polymer (CA) used in the comparative example described later was also determined in the same manner.

[0080] [Melting point (Tm), endothermic end temperature (TmE), exothermic start temperature (TcS), crystallization temperature (Tc)] Using a DSC measuring device (DSC220C) manufactured by Seiko Instruments Inc., exothermic and endothermic curves were obtained in accordance with ASTM D3418, and the melting point (Tm), endothermic end temperature (TmE), exothermic start temperature (TcS), and crystallization temperature (Tc) were determined as follows.

[0081] Approximately 5 mg of the sample was placed in a measurement aluminum pan, heated from 20°C to 280°C at a heating rate of 10°C / min, held at 280°C for 5 minutes, cooled to 20°C at a cooling rate of 10°C / min, held at 20°C for 5 minutes, and then heated again from 20°C to 280°C at a heating rate of 10°C / min. The crystallization peak that appeared during the first cooling was taken as the crystallization temperature (Tc). When multiple crystallization peaks were detected, the one with the highest temperature was taken as the crystallization temperature (Tc). The melting peak that appeared during the second heating was taken as the melting point (Tm). When multiple melting peaks were detected, the one with the highest temperature was taken as the melting point (Tm).

[0082] The temperature at which the endotherm of the melting (endotherm) curve ended was taken as the endotherm end temperature (TmE), and the temperature at which the heat generation of the crystallization (exotherm) curve started was taken as the exotherm start temperature (TcS).

[0083] The start and end points are the points at which it can be confirmed that the curve deviates from the baseline where the amount of heat becomes constant at the start or end of endothermic or exothermic reaction, and a difference in the amount of heat begins to appear.

[0084] <Preparation Example 1: Preparation of (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride> Using the method described in Preliminary Experiment 5 (paragraphs 0346 to 0348) of WO 2014 / 123212, (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride was synthesized.

[0085] [Production Example 1] (Production of modified 4-methyl-1-pentene polymer (A1)) [Synthesis Example 1: Production of Olefin Polymerization Catalyst] At 30°C, in a 200mL three-necked flask equipped with a stirrer and fully purged with nitrogen, 30mL of purified decane and 14.65mmol of particulate solid polymethylaluminoxane with a D50 of 28μm and an aluminum atom content of 43% by mass (synthesized using the method described in International Publication No. 2014 / 123212) were charged under nitrogen gas flow to form a suspension. 50.0mg (0.0586mmol) of (8-octamethylfluoren-12'-yl-(2-(adamantan-1-yl)-8-methyl-3,3b,4,5,6,7,7a,8-octahydrocyclopenta[a]indene))zirconium dichloride obtained in Preparation Example 1 was added to the suspension as a 4.58mmol / L toluene solution while stirring. After 1 hour, stirring was stopped, and the resulting mixture was washed with 100 mL of decane by decantation, and then decane was added to make 50 mL of a slurry liquid (zirconium atom carrying rate: 98%).

[0086] [Synthesis Example 2: Preparation of prepolymerization catalyst component] To the slurry liquid prepared in Synthesis Example 1, 1.0 mL of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atom) was charged under a nitrogen gas flow at 25°C. After cooling to 15°C, 10 mL of 4-methyl-1-pentene was charged into the reactor over 60 minutes. The start of the charging of 4-methyl-1-pentene was regarded as the start of prepolymerization. Stirring was stopped 2.0 hours after the start of prepolymerization, and the resulting mixture was washed three times with 100 mL of decane by decantation. The prepolymerization catalyst component was a decane slurry (9.5 g / L, 0.56 mmol / L in terms of zirconium atom).

[0087] [Production of 4-methyl-1-pentene polymer (A1a)] At room temperature and under a nitrogen stream, 425 mL of purified decane was placed in a SUS polymerization vessel equipped with a stirrer having an internal volume of 1 L, and the temperature was raised to 40°C. After reaching 40°C, 0.8 mL (0.4 mmol in terms of aluminum atoms) of a decane solution of triisobutylaluminum (TIBAL) (0.5 mmol / mL in terms of aluminum atoms) was charged, and then 0.00175 mmol of the decane slurry of the prepolymerization catalyst component of Synthesis Example 2 was charged in terms of zirconium atoms. 23.75 NmL of hydrogen was charged, and then a mixture of 230 mL of 4-methyl-1-pentene and 22.4 mL of Linearene 168 (Idemitsu Kosan, a mixture of 1-hexadecene and 1-octadecene) was continuously charged into the polymerization vessel at a constant rate over 2 hours. The start of charging the mixture was regarded as the start of polymerization, and the temperature was maintained at 45°C for 4.5 hours. 23.75 NmL of hydrogen was charged 1 hour and 2 hours after the start of polymerization. 4.5 hours after the start of polymerization, the temperature was lowered to room temperature, the pressure was released, and the polymerization liquid containing a white solid was immediately filtered to obtain a solid substance. This solid substance was dried under reduced pressure at 80°C for 8 hours to obtain a 4-methyl-1-pentene polymer (A1a). The yield was 142 g.

[0088] The content of structural units in the 4-methyl-1-pentene polymer (A1a) was 96.5 mol% of structural units derived from 4-methyl-1-pentene, and the total amount of structural units derived from α-olefins was 3.5 mol%. The melting point (Tm) of the polymer (A1a) was 201°C, and the intrinsic viscosity [η] (in decalin at 135°C) was 4.2 dl / g.

[0089] [Production of modified 4-methyl-1-pentene polymer (A1)] 100 parts by mass of 4-methyl-1-pentene polymer (A1a), 2 parts by mass of maleic anhydride, and 0.02 parts by mass of 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3 (Perhexyne 25B, manufactured by NOF Corp.) as an organic peroxide were blended and kneaded using a Labo Plastomill mixer manufactured by Toyo Seiki Seisakusho Co., Ltd. at a resin temperature of 280°C and a screw rotation speed of 150 rpm to obtain a modified 4-methyl-1-pentene polymer (A1).

[0090] The amount of structural units in the modified 4-methyl-1-pentene polymer (A1) was the same as that of the 4-methyl-1-pentene polymer (A1a). The melting point (Tm) of the modified 4-methyl-1-pentene polymer (A1) was 201°C, the intrinsic viscosity [η] (in decalin at 135°C) was 0.9 dl / g, and the amount of graft modification was 1.5 mass%. Other physical properties of the modified 4-methyl-1-pentene polymer (A1) are shown in Table 1-1. In the following description, Table 1-1 and Table 1-2 are collectively referred to as Table 1. In the following description, the modified 4-methyl-1-pentene polymer (A1) may be simply referred to as "polymer (A1)" or "polymer A1", and similar abbreviations may be used for other modified 4-methyl-1-pentene polymers.

[0091] [Manufacturing Examples 2 to 7] (Production of modified 4-methyl-1-pentene polymers (A2) to (A7)) In the production example of the modified 4-methyl-1-pentene polymer (A1), the α-olefin type, the amount of the structural unit derived from the α-olefin, and the amount of graft modification were changed as shown in Table 1, but the same procedure as in the production example of the modified 4-methyl-1-pentene polymer (A1) was followed to obtain modified 4-methyl-1-pentene polymers (A2) to (A7).

[0092] [Production Example 8] (Production of modified 4-methyl-1-pentene polymer (CA8)) According to the polymerization method described in Comparative Example 9 of WO 2006 / 054613, a 4-methyl-1-pentene polymer (CA8a) was obtained by changing the ratio of 4-methyl-1-pentene, other comonomers (a mass mixture of 1-hexadecene, 1-octadecene, etc.), and hydrogen. A modified 4-methyl-1-pentene polymer (CA8) was obtained in the same manner as in the production example of the modified 4-methyl-1-pentene polymer (A1), except that the 4-methyl-1-pentene polymer (A1a) was changed to a 4-methyl-1-pentene polymer (CA8a) and the amount of graft modification was changed as shown in Table 1.

[0093] [Production Example 9] (Production of 4-methyl-1-pentene polymer (CA9)) In Comparative Example 7 of WO 2006 / 054613, the amount of monomer charged was changed so that the content of structural units derived from 4-methyl-1-pentene and 1-decene in the resulting copolymer was the content shown in Table 1 below, and the amount of hydrogen during polymerization was adjusted so that the composition and physical properties were as shown in Table 1 below, thereby obtaining a copolymer of 4-methyl-1-pentene and 1-decene (CA9). The physical properties are shown in Table 1. The 4-methyl-1-pentene polymer (CA9) was also used in the base layer (I) used in the examples and comparative examples described below. TPX ) is used in the formation of

[0094] [Table 1-1]

[0095] [Table 1-2]

[0096] <Preparation of coating agent and evaluation of stability> [Preparation Example 1: Preparation of Coating Agent (X1)] To 10 g of the modified 4-methyl-1-pentene polymer (A1) (i.e., the mass of the modified 4-methyl-1-pentene polymer (A1) is taken as 100% by mass), 0.1% by mass of tri(2,4-di-t-butylphenyl)phosphate as an antioxidant and 0.1% by mass of n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate as a heat stabilizer were added, and methylcyclohexane (manufactured by Wako Pure Chemical Industries, Ltd.) and ethyl acetate (manufactured by Wako Pure Chemical Industries, Ltd.) were added as a solvent in a mass ratio of 8:2 so that the solid content concentration became 5% by mass, and the mixture was stirred at 60°C for 3 hours at 200 pm to prepare a coating agent (X1) containing the modified 4-methyl-1-pentene polymer (A1) and not containing an isocyanate compound.

[0097] [Preparation of coating agents (X2) to (X7) and (CX8)] Except for using any of the polymers (A2) to (A7) and (CA8) instead of the polymer (A1), coating agents were prepared in the same manner as in Preparation Example 1. The types of polymers contained in each coating agent are shown in Tables 2-1 and 2-2. In the following description, Tables 2-1 and 2-2 are collectively referred to as Table 2.

[0098] [Preparation Example 2: Preparation of Coating Agent (XA1)] After cooling the coating agent (X1) to 23°C, 0.2 mass% of Takenate D170N (manufactured by Mitsui Chemicals, Inc.) (where the mass of the polymer (A1) in the coating agent is taken as 100 mass%) was added and stirred at 200 rpm for 5 minutes to prepare a coating agent (XA1) containing the polymer (A1) and an isocyanate compound.

[0099] [Preparation of coating agent (XA4)] A coating agent was prepared in the same manner as in Preparation Example 2, except that the coating agent (X4) was used instead of the coating agent (X1).

[0100] [Preparation of coating agent (XA5)] A coating agent was prepared in the same manner as in Preparation Example 2, except that the coating agent (X5) was used instead of the coating agent (X1).

[0101] [Storage stability of coating agent] Each of the obtained coating agents was stored at room temperature (23° C.) for 3 days from immediately after preparation, and then visually evaluated according to the following evaluation criteria. The evaluation results are shown in Table 2. (Evaluation Criteria) ◯: The coating agent was transparent to the naked eye under visible light and had flowability. Δ: The coating agent was cloudy when visually examined under visible light, but had fluidity. ×: No fluidity was observed regardless of whether the coating agent was transparent or opaque when visually examined under visible light.

[0102]

Table 2-1

[0103]

Table 2-2

[0104] [Example 1] <Preparation of a substrate layer (I) mainly composed of TPX TPX ) The 4-methyl-1-pentene polymer (CA9) obtained in Production Example 9 was formed into a film at a cylinder temperature of 270°C and a chill roll temperature of 60°C using a cast film forming machine equipped with a T-die, thereby preparing a substrate layer (I TPX ) with a thickness of 100 μm. The prepared substrate layer (I TPX ) was described as "TPX" in Table 3-1. In the following description, Tables 3-1 to 3-4 are collectively referred to as Table 3.

[0105] [Preparation of a laminate] The applicator was adjusted to make the primer layer (II) about 1.0 μm thick. Then, the coating agent (X1) was applied to the substrate layer (I TPX ) obtained as described above, and dried at 100°C for 20 seconds to form a coating film, thereby obtaining a laminate in which the primer layer (II) was laminated on the substrate layer (I TPX ).

[0106] The laminate was placed on the metal plate such that the primer layer (II) was on top (i.e., the metal plate was in contact with the substrate layer (I TPX )). Further, an aluminum sheet (thickness: 0.5 mm) manufactured by UACJ Foil Co., Ltd. was placed on the primer layer (II) side. Then, a metal plate was placed on the aluminum sheet, and pressing was performed at a temperature of 180°C and a pressure of 5 MPa for 5 minutes using a press molding machine manufactured by Toyo Seiki Seisakusho Co., Ltd. From the press machine, the substrate layer (I TPX), a primer layer (II), and a top layer (III) were laminated in this order and then taken out.

[0107] [Adhesion between the top layer (III) and the primer layer (II)] The laminate removed from the press was cut into test pieces with a width of 15 mm. The top layer (III) of the test piece was peeled from the primer layer (II) at a test speed of 50 mm / min and an angle of 90° using a universal material testing machine at room temperature (23°C), and the adhesion between the top layer (III) and the primer layer (II) was evaluated using the peel stress at that time according to the following evaluation criteria. The evaluation results are shown in Table 3-1. In the following description, Tables 3-1 to 3-4 are collectively referred to as Table 3. (Evaluation Criteria) ◯: The peel stress was 0.2 N / cm or more, or no peeling occurred. ×: The peel stress was less than 0.2 N / cm.

[0108] [Examples 2 to 7] Except for using the coating agents (X2) to (X7) instead of the coating agent (X1) in the preparation of the primer layer (II), laminates were prepared and evaluated in the same manner as in Example 1. The results are shown in Table 3.

[0109] [Example 8] Except for using a copper foil having a thickness of 40 μm and a surface roughness of 0.5 μm for the top layer (III), a laminate was produced and evaluated in the same manner as in Example 1. The results are shown in Table 3.

[0110] [Examples 9 to 10] In the preparation of the primer layer (II), except that the composition coating agent (X4) or the coating agent (X5) was used instead of the coating agent (X1), a laminate was prepared and evaluated in the same manner as in Example 8. The results are shown in Table 3.

[0111] [Example 11] A polyester film (Lumirror (registered trademark) S10 manufactured by Toray Industries, Inc., described as "PET" in Table 2) was used as the substrate layer (I), and the coating agent (XA1) was applied and uniformly spread with an applicator, followed by drying at 100°C for 20 seconds to prepare a primer layer (II). The film was then further dried at 80°C for 20 hours (aging treatment). After the aging treatment, an aluminum sheet (thickness 0.5 mm) was placed on the primer layer (II) side in the same manner as in Example 1 to obtain a laminate. That is, in Example 11, the aluminum sheet becomes the top layer (III). The selected laminate was evaluated in the same manner as in Example 1. The results are shown in Table 3.

[0112] [Examples 12 to 13] A laminate was prepared and evaluated in the same manner as in Example 11, except that the coating agent (XA4) or the coating agent (XA5) was used instead of the coating agent (XA1) in the preparation of the primer layer (II). The results are shown in Table 3.

[0113] [Example 14] Except for using copper foil instead of an aluminum sheet as the top layer (III), a laminate was produced and evaluated in the same manner as in Example 11. The results are shown in Table 3.

[0114] [Examples 15 to 16] A laminate was prepared and evaluated in the same manner as in Example 14, except that the coating agent (XA4) or the coating agent (XA5) was used instead of the coating agent (XA1) in the preparation of the primer layer (II). The results are shown in Table 3.

[0115] [Example 17] A laminate having a primer layer (II) laminated on a base layer (I) was prepared in the same manner as in Example 1, except that the same copper foil as that used as the top layer (III) in Example 8 was used as the base layer (I). The laminate was placed on the metal plate so that the primer layer (II) was on top (i.e., the metal plate was in contact with the copper foil that would become the base layer (I)). Furthermore, a prepreg (MEGTRON6 R-5670 manufactured by Panasonic Corporation) in which a polyphenylene ether (PPE) resin was impregnated into glass fiber was used as the top layer (III) on the primer layer (II) side, and the primer layer (II) and the top layer (III) were placed in close contact with each other. Thereafter, a metal plate was placed on the prepreg, and the prepreg was thermally cured by pressing for 10 hours at a pressure of 5 MPa while applying a temperature of 180°C using a press molding machine manufactured by Toyo Seiki Seisakusho Co., Ltd. The laminate in which the base layer (I), primer layer (II), and top layer (III) were laminated in this order was taken out of the press machine, and evaluation was performed in the same manner as in Example 1. The results are shown in Table 3.

[0116] [Examples 18 to 19] A laminate was prepared and evaluated in the same manner as in Example 17, except that the coating agent (X4) or the coating agent (X5) was used instead of the coating agent (X1) in the preparation of the primer layer (II). The results are shown in Table 3.

[0117] [Examples 20 to 22] A laminate was produced and evaluated in the same manner as in Example 17, except that in the production of the primer layer (II), coating agent (XA1), coating agent (XA4), or coating agent (XA5) was used instead of coating agent (X1). The results are shown in Table 3. The heat curing process of the prepreg, which is carried out in the same manner as in Example 17, also serves as an aging treatment between the primer (II) formed from coating agent (XA1), coating agent (XA4), or coating agent (XA5) and the base layer (I).

[0118] [Comparative Example 1] A laminate was prepared and evaluated in the same manner as in Example 1, except that the coating agent (CX8) was used instead of the coating agent (X1) used in preparing the primer layer (II). However, the coating agent (CX8) in which the polymer CA8 was dissolved had poor storage stability. TPX Even if the coating agent (CX8) was applied on the base layer (I), a good layer could not be formed. TPX Since no coating layer was formed on the aluminum sheet (III) in the same manner as in Example 1, it was also not possible to form a top layer (III) using an aluminum sheet in the same manner as in Example 1. The results are shown in Table 3. Items that were not evaluated are marked in Table 3 as "evaluation not possible."

[0119] [Comparative Example 2] A substrate layer (I TPX ) was prepared, and the obtained substrate layer (I TPX An aluminum sheet was placed directly on the base layer (I). Then, a metal plate was placed on the aluminum sheet, and pressed for 5 minutes at a pressure of 5 MPa and a temperature of 180°C using a press molding machine manufactured by Toyo Seiki Seisakusho Co., Ltd. TPX ) and an aluminum sheet to be the top layer (III) were laminated in this order, and a laminate was taken out. The laminate taken out was evaluated in the same manner as in Example 1. The results are shown in Table 3.

[0120] [Comparative Example 3] Except for changing the aluminum sheet used as the top layer (III) to the same copper foil as used in Example 8, a laminate of Comparative Example 3 was prepared in the same manner as in Comparative Example 2, and evaluated in the same manner as in Example 1. The results are shown in Table 3.

[0121] [Comparative Example 4] A laminate of Comparative Example 4 was prepared in the same manner as in Comparative Example 2, except that a polyester film (Lumirror (registered trademark) S10 manufactured by Toray Industries, Inc.) was used as the base layer (I), and was evaluated in the same manner as in Example 1. The results are shown in Table 3.

[0122] [Comparative Example 5] A laminate of Comparative Example 5 was obtained in the same manner as in Comparative Example 3, except that a polyester film (Lumirror (registered trademark) S10 manufactured by Toray Industries, Inc.) was used as the base layer (I), and was evaluated in the same manner as in Example 1. The results are shown in Table 3.

[0123] [Table 3-1]

[0124] [Table 3-2]

[0125] [Table 3-3]

[0126] [Table 3-4]

Claims

1. A laminate comprising a base layer (I), a primer layer (II), and a top layer (III) laminated in this order, The primer layer (II) contains a modified 4-methyl-1-pentene polymer (A) that satisfies the following requirements (A-1) and (A-3): (A-1) The amount (U1) of the structural unit (i) derived from 4-methyl-1-pentene is 84.0 to 100.0 mol %, and the total amount (U2) of the structural units (ii) derived from an α-olefin having 2 to 20 carbon atoms (excluding 4-methyl-1-pentene) is 16.0 to 0.0 mol % (the total of U1 and U2 is 100.0 mol %). (A-3) The melting point (Tm) measured by a differential scanning calorimeter (DSC) is more than 180° C. and 220° C. or less.

2. 2. The laminate according to claim 1, wherein the amount of graft modification of the modified 4-methyl-1-pentene polymer (A) is more than 0.0% by mass and not more than 5.0% by mass.

3. 2. The laminate according to claim 1, wherein the α-olefin (excluding 4-methyl-1-pentene) from which the structural unit (ii) is derived has 4 to 20 carbon atoms.

4. 2. The laminate according to claim 1, wherein U1 is 92.5 to 97.1 mol % and U2 is 7.5 to 2.9 mol % (wherein the sum of U1 and U2 is 100.0 mol %).

5. The laminate according to claim 1, wherein the modified 4-methyl-1-pentene polymer (A) satisfies at least one of the following requirements (A-4) and (A-5): (A-4) In the measurement of the melting point (Tm) by a differential scanning calorimeter (DSC), the endothermic end temperature (TmE) in the melting (endothermic) curve is 230° C. or lower. (A-5) In the measurement of the melting point (Tm) by a differential scanning calorimeter (DSC), the heat generation onset temperature (TcS) in the crystallization (heat generation) curve is 210° C. or lower.

6. The laminate according to claim 5, wherein the modified 4-methyl-1-pentene polymer (A) satisfies the requirements (A-4) and (A-5).

7. The laminate according to claim 1, wherein the modified 4-methyl-1-pentene polymer (A) satisfies the following requirement (A-2): (A-2) The intrinsic viscosity [η] measured in decalin at 135° C. is in the range of 0.5 to 6.0 dl / g.

8. The laminate according to any one of claims 1 to 7, wherein the substrate layer (I) comprises at least one selected from the group consisting of a resin, a metal, and a prepreg.

9. The laminate according to any one of claims 1 to 7, wherein the top layer (III) comprises at least one selected from the group consisting of a resin, a metal, and a prepreg.

Citation Information

Patent Citations

  • laminate

    JP2016168849A

  • laminate

    JP2017065270A